A cost analysis of producing vaccines in developing countries. Issue 9 (21st February 2019) - Munira, Syarifah Liza; Hendriks, Jan T.; Atmosukarto, Ines I.; Friede, Martin H.; Carter, Louise M.; Butler, James R.G.; Clements, Archie C.A.
Abstract: Developing country vaccine manufacturers (DCVMs) supply over half of the vaccines used in developing country immunisation programs. Decisions by developing countries to establish vaccine manufacturing should be based on economic viability, however reliable assessments of vaccine production costs are lacking. This study aimed to quantify the cost of establishing vaccine manufacturing facilities and producing vaccines in developing countries. This study estimates vaccine production costs in developing countries based on twelve vaccines produced by eight DCVMs. The results were based on estimates of the capital and operating costs required to establish vaccine manufacturing facilities under three hypothetical scenarios of production scale and scope. Cost patterns were then compared to vaccine prices paid by countries in both industrialized and developing country markets. The cost of producing vaccines in developing countries was estimated to be on average US 2.18 per dose, ranging between US 0.98 and US 4.85 for different vaccine types and formulations. Vaccine costs-per-dose decrease as production scale and scope increase. Cost-per-dose is mainly driven by fixed costs, but at a scale of production over 20 million doses per year it becomes driven by variable costs. Under the three hypothetical scenarios used, costs-per-dose of vaccines produced by developing countries were around 47% lower than vaccine prices in developing-country markets and 84% lower than prices in industrialized-country markets. This study has found that local production of vaccines in developing countries exhibits both economies of scale and economies of scope. The lower costs relative to prices suggests that a producer surplus and potential profits may be attainable in both developing and developed country markets, supporting sustainable production.